Ochratoxin A: Developmental and Reproductive Toxicity—An Overview. (6th January 2014) - Malir, Frantisek; Ostry, Vladimir; Pfohl‐Leszkowicz, Annie; Novotna, Eva
<x xml:space="preserve">Abstract</x> Ochratoxin A (OTA) is nephrotoxic, hepatotoxic, reprotoxic, embryotoxic, teratogenic, neurotoxic, immunotoxic, and carcinogenic for laboratory and farm animals. Male and female reproductive health has deteriorated in many countries during the last few decades. A number of toxins in environment are suspected to affect reproductive system in male and female. OTA is one of them. OTA has been found to be teratogenic in several animal models including rat, mouse, hamster, quail, and chick, with reduced birth weight and craniofacial abnormalities being the most common signs. The presence of OTA also results in congenital defects in the fetus. Neither the potential of OTA to cause malformations in human nor its teratogenic mode of action is known. Exposure to OTA leads to increased embryo lethality manifested as resorptions or dead fetuses. The mechanism of OTA transfer across human placenta (e.g., which transporters are involved in the transfer mechanism) is not fully understood. Some of the toxic effects of OTA are potentiated by other mycotoxins or other contaminants. Therefore, OTA exposure of pregnant women should be minimized. OTA has been shown to be an endocrine disruptor and a reproductive toxicant, with abilities of altering sperm quality. Other studies have shown that OTA is a testicular toxin in animals. Thus, OTA is a biologically plausible cause of testicular cancer in man.